Continuous terrain remodelling: gaining the upper hand in cyber defence. Issue 2 (3rd May 2020) - Matania, Eviatar; Tal-Shir, Eldad
ABSTRACT: This paper seeks to shed light on the implications of the malleability of cyberspace for the offence-defence balance. We argue that defenders' authority over their 'cyber terrain' which results from genuine ownership of its comprising assets gives them a unique advantage over attackers. Namely, the advantage to alter the state and composition of any assets over which cyberattackers and defenders contend. We suggest that this advantage is optimally suited for employment in a defensive paradigm of continuous remodelling of the cyber terrain (CTR). We demonstrate that various technologies are emerging as potential facilitators of such an approach to cyber defence. We also substantiate CTR's capacity for granting defenders the upper hand by demonstrating its thwarting of most phases of cyberattacks and the imposition of an asymmetric disadvantage on attackers. Specifically, we analyse the promise of such remodelling in light of Lockheed Martin's cyber kill chain model, and exemplify its disruptive effects on infamous malware. We also discuss what constitutes an owner's cyber terrain in the age of the cloud, the obstacles to CTR, its implications for the industry, and propose an expected trajectory for offensive actions in cyberspace in an era of terrain remodelling.